Evektivitas Phet Simulation Sebagai Media Pembelajaran Fisika Dasar I Mahasiswa S1 Pendidikan IPA - I Ketut Mahardika; Elvina Camelia; Imilda Ailiyah Fatikhah; Fatah An Naufal; Reza Yunita Pratiwi; Rizka Elan Fadilah; Firdha Yusmar (Jurnal Ilmiah Wahana Pendidikan, 2022)
The rapid development of science and technology provides an alternative in learning, one of which is the use of PhET media. The use of PhET or Physics Education Technology, a media that contains physics learning animations. So that the material studied is easier to understand and looks more real. This study aims to determine the effectiveness of using PhET as a learning medium for Basic Physics 1 course. This research is aimed at undergraduate students in Science Education at the University of Jember who are taking Basic Physics I course. The method used in this research is quantitative data analysis in the form of a survey using questionnaire tests through Google Form media, as well as using literature studies. The results of the study stated that the use of PhET as a learning medium was considered effective enough to be applied and could improve students' understanding of the material.